PENGARUH PERECANAAN PAJAK DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Kasus Pada Perusahaan Manufaktur Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2019) - Ony Widilestariningtyas; Nadia Ana Sekarini (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2022)
The study was conducted to determine whether tax planning and company size affect earnings management in manufacturing companies in the food and beverage sector. Earnings management listed on the Indonesia Stock Exchange (IDX) in 2018 and 2019. The research method used is descriptive and verification methods with a quantitative approach. The population in this study is the food and beverage sub-sector companies. The sampling technique used is purposive sampling technique. The method of data analysis in this study used multiple linear regression analysis which was tested using SPSS 26.0 for Windows software. Based on the research conducted, it can be seen that tax planning has a positive and significant effect on earnings management and firm size has a positive and significant effect on earnings management.